Vehicle Accident Prevention System Embedded With Alcohol Detector - Mohamad, Mas Haslinda; Hasanuddin, Mohd Amin; Ramli, Mohd Hafizzie (Yanam Eoryx Publications, 2013)
The purpose of this project is to develop vehicle accident prevention by method of alcohol detector in an effort to reduce traffic accident cases based on driving under the influence alcohol.This project is developed by integrated the alcohol sensor with the microcontroller. The alcohol sensor used in this project is MQ-3 which to detect the present of alcohol content in human breath.An ignition system which will produce spark plugs is build up as a prototype to act like the ignition starter over the vehicle’s engine.The ignition system will operate based on the level of blood alcohol content (BAC) from human breaths detected by alcohol sensor.